DAMPAK STRUKTUR KEPEMILIKAN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Sri Sudarsi; Moch Irsad; Andi Kartika (JURNAL STIE SEMARANG, 2022)
The aim of the research is to analyze managerial ownership, institutional ownership, profitability and the size of the company affecting a company's debt policy. This research uses the manufacturing sector listed on the Indonesia Stock Exchange (IDX) The type of data used is secondary data with proposed sampling data collection techniques, namely companies that have managerial ownership, institutional ownership and have complete data, so that the sample number of 135 companies. Based on the results obtained that managerial ownership, institutional ownership has a significant negative influence on debt policy. The size of the company has a positive effect on the debt policy, while profitability has no effect on the debt policy.